Impact of coffee silverskin on in-vitro viability of kefir culture during storage - Sine Ozmen-Togay; Gunnur Gulkun; Nurcan Degirmencioglu; Metin Guldas; Elif Yildiz; Yasemin Sahan; Ozan Gurbuz (Mljekarstvo)
Probiotic dairy products must contain a certain level of live probiotic microorganisms at the time of consumption. The number of live microorganisms in kefir culture, which is a mixture of different microorganisms, may change during storage due to various factors. In this study, the effects of adding a novel ingredient coffee bean membrane (CSS-coffee silverskin), on the viability of microorganisms contained in kefir culture were investigated. For this purpose, CSS obtained from 2 different coffee varieties (Arabica and Robusta) was added to kefir samples at 3 different concentrations (0.5, 0.75 and 1.0 %) at the beginning of fermentation. It was observed that especially the addition of CSS belonging to the Robusta variety significantly increased the viability of lactic acid bacteria (lactobacilli and lactococci) which accounted for 88-94.10 % and 82.37-92.44 % respectively. During the storage period of 28 days at 4 °C; it could be observed that kefir enrichment with CSS of both coffee varieties increased the viability of lactobacilli and lactococci after in-vitro digestion, depending on the rate of supplementation. Number of yeasts was decreased during the storage.